Robust power control for PV and battery systems: integrating sliding mode MPPT with dual buck converters - Fekik, Arezki; Hamida, Mohamed Lamine; Azar, Ahmad Taher; Ghanes, Malek; Hakim, Arezki; Denoun, Hakim; Hameed, Ibrahim A. (Frontiers in Energy Research, 2024)
This research is focused on optimizing the power extraction from solar panels through the implementation of sliding mode control in a buck converter. The generated energy is utilized for charging a battery, and a buck-boost converter is integrated to regulate the current based on a reference established by a PI controller. A supervisory system manages the power supply of the buck-boost converter according to the battery charge level and available solar power. Specific operating conditions, such as insufficient solar power, are addressed through battery intervention. This innovative approach aims to maximize the efficiency of solar energy production while preserving the battery's lifespan. The validation of this hybrid topology, conducted through simulations on MATLAB using two converters (buck and buck-boost), significantly contributes to the advancement of sustainable and efficient energy solutions in a professional and academic context.